La brecha digital y el desarrollo humano sostenible. Propuesta de un proyecto de telecentro en la parroquia Canchagua, cantón Saquisilí provincia de Cotopaxi. - Cantuña Flores, Karla Susana (2011)
The null or poor access to information and telecommunications services has evolved during the existence of the digital divide in each of the rural and marginal urban areas of our country, this has prevented the achievement of human development and hence the lack of a better quality of life of the population. This study adopts the theoretical framework related to the digital divide and human development. This research has to propose a strategy to reduce the digital divide through a project Telecentre to permit inclusion and social appropriation of the ICT benefiting the residents of the parish Canchagua canton Saquisilí of Cotopaxi province, based on a infrastructure last mile of optical fiber. Apply a methodology that integrates indicators key ICT published in the World Summit on the Information Society in the work of the Partnership on Measuring ICT for Development 2010.